Two new species of Cyrtodactylus Gray, 1827 (Squamata: Gekkonidae) from a karstic archipelago in the Salween Basin of southern Myanmar (Burma) - Grismer, L. Lee; Wood, Perry L. Jr.; Quah, Evan S. H.; Grismer, Marta S.; Thura, Myint Kyaw; Oaks, Jamie R.; Lin, Aung (Zootaxa, 2020)
An integrative taxonomic analysis of the 10 species of the Cyrtodactylus sinyineensis group based on squamation, color pattern, and the mitochondrial gene NADH dehydrogenase subunit 2 (ND2) and its flanking tRNA regions, recovered the newly discovered populations from Datt Kyaik and Taung Wine Hills in Kayin State as the new species Cyrtodactylus dattkyaikensis sp. nov. and C. taungwineensis sp. nov. The Maximum Likelihood and Bayesian phylogenetic estimates supported C. dattkyaikensis sp. nov. as the sister species of C. bayinnyiensis and C. taungwineensis sp. nov. as the sister species of C. sinyineensis. Each new species is differentially diagnosable from all other C. sinyineensis group species based on their morphological placement in multivariate space and several statistically significant mean differences is meristic squamation and color pattern data. The C. sinyineensis group ranges across an archipelago of karstic habitat-islands in the Salween Basin of southern Myanmar. The discovery of these new species continues to underscore the unprecedented high degree of diversity and site-specific endemism in this relatively small region and the urgent need for the conservation of its karstic terranes.